2016
DOI: 10.4314/njp.v43i1.1
|View full text |Cite
|
Sign up to set email alerts
|

A review of the literature on childhood Burkitt lymphoma in Nigeria

Abstract: Background: Burkitt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Though said to be the most common childhood malignant tumour in Nigeria, Burkitt lymphoma was not common in the present study as well as in the afore mentioned Lagos series as it represented 2.2% and 1.1% of cancers seen respectively [14,25]. The decline in the frequency of Burkitt lymphoma in some centres within Nigeria has been reported, and has been attributed to improvement in living conditions and better malaria control measures, given the role of malaria in endemic Burkitt lymphoma [14,25].…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Though said to be the most common childhood malignant tumour in Nigeria, Burkitt lymphoma was not common in the present study as well as in the afore mentioned Lagos series as it represented 2.2% and 1.1% of cancers seen respectively [14,25]. The decline in the frequency of Burkitt lymphoma in some centres within Nigeria has been reported, and has been attributed to improvement in living conditions and better malaria control measures, given the role of malaria in endemic Burkitt lymphoma [14,25].…”
Section: Discussioncontrasting
confidence: 43%
“…On the other hand, Burkitt lymphoma (26.2%) was the most prevalent cancer among children in the Uyo study, followed by nephroblastoma (14.3%), and was 3rd most frequent cancer (13.2%), after retinoblastoma (26.4%) and rhabdomyosarcoma (14.3%) in a study in Ibadan [16,24]. Though said to be the most common childhood malignant tumour in Nigeria, Burkitt lymphoma was not common in the present study as well as in the afore mentioned Lagos series as it represented 2.2% and 1.1% of cancers seen respectively [14,25]. The decline in the frequency of Burkitt lymphoma in some centres within Nigeria has been reported, and has been attributed to improvement in living conditions and better malaria control measures, given the role of malaria in endemic Burkitt lymphoma [14,25].…”
Section: Discussionmentioning
confidence: 40%
“…1 In Nigeria, it is one of the most common cause of admissions for childhood malignancies with hospital prevalence ranging between 18.3 and 65 percent of all paediatric cancer-related admissions. 2 Previous study from AKTH reported 29.8% prevalence of BL in a retrospective cohort of children admitted with malignancy 3 . Burkitt lymphoma is potentially curable disease, with cure rate exceeding 90% in high-income settings however, in low income countries where majority of affected children live, the cure rate is less than 35%.…”
Section: Introductionmentioning
confidence: 93%
“…It may actually not be surprising that Burkittt's lymphoma is on the decline because of efforts been made in African towards the eradication of malaria which play a role in its pathogenesis [60,61,62]. It is possible that the decline in Bukitt's lymphoma is a reflection of the gains been achieved [60,61,62]. More so Ocheni et al [18] and Ojesina et al [19] in eastern and western Nigeria respectively have all demonstrated similar decline in Burktt's lymphoma relative to other malignancies.…”
Section: Discussionmentioning
confidence: 99%